Analysis of the Effect of Ownership Structure, Leverage, Profitability, and Dividend Policy on Earnings Management with Audit Quality Moderation in Manufacturing Companies - Pertiwi, Ade Dwi; Erwin, Keulana; Azhar, Ibnu Austrindanney Sina (Empiricism Journal, 2026)
This study aims to analyze the influence of managerial ownership, leverage, profitability, and dividend policy on earnings management, with audit quality as a moderating variable in manufacturing companies. This study employed a quantitative approach with a causal associative method. The study population was manufacturing companies listed on the Indonesia Stock Exchange (IDX), with a sample of 220 observations selected using a purposive sampling technique. The data used were secondary data obtained from the companies’ annual financial reports. Data analysis was performed using multiple linear regression and moderated regression analysis (MRA) with the assistance of IBM SPSS Statistics 26 software. The results showed that managerial ownership, leverage, profitability, and Dividend Policy had no significant partial effect on earnings management. Furthermore, the Moderated Regression Analysis (MRA) results indicated that audit quality was unable to moderate the influence of managerial ownership, leverage, profitability, or dividend policy on earnings management. Audit quality also had no direct effect on earnings management. This finding indicates that earnings management practices in manufacturing companies are more influenced by other factors outside the research model, such as corporate governance mechanisms, internal control effectiveness, management characteristics, and other external factors.